Psychological support post-release of humanitarian workers taken hostage: the experience of the International Committee of the Red Cross (ICRC). Issue 3 (3rd May 2020) - Aebischer Perone, S.; Althaus, F.; Chappuis, F.; Aguirre Zimerman, N.; Martinez, E.; Regel, S.
ABSTRACT: Following release, former hostages face many challenges and may struggle to regain control over their lives. Research and evidence on how to effectively address the needs of hostages during their release and afterwards is lacking. The International Committee of the Red Cross has extensive experience in managing hostage situations and has strengthened the practice of care offered to its own affected staff by developing an inter-professional comprehensive seven phase care model adapted to incidents of extended duration with multiple stressors. This includes strong coordination between the different actors involved, combined with long-term peer, social and organisational support, as well as workplace reintegration with guidance by colleagues, and specialised counselling when necessary, to ensure positive outcomes, and minimise permanent sequelae.